2017
DOI: 10.1111/1471-0528.14469
|View full text |Cite
|
Sign up to set email alerts
|

The influence of age at menarche, menstrual cycle length and bleeding duration on time to pregnancy: a large prospective cohort study among rural Chinese women

Abstract: A later menarche, longer cycle, shorter or longer bleeding duration were associated with lower fecundity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 44 publications
(54 reference statements)
0
17
0
2
Order By: Relevance
“…Importantly, we show that a cycle length of 28 days is not common for many women, which is usually the reference length for a typical woman. Comparatively, previous analyses among women using fertility apps or cohort studies have reported that the mean or median cycle length for all women ranged between 28 and 30 days [ 8 , 11 , 33 , 34 ], and studies reporting on actual cycles reported means between 27.7 and 29.6 days [ 2 , 4 , 5 , 7 , 35 ]. These results cannot be extrapolated to an individual woman, and clinically, it is not helpful, as we have clearly demonstrated that the percentage of women with an average cycle length of 28 days is uncommon.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Importantly, we show that a cycle length of 28 days is not common for many women, which is usually the reference length for a typical woman. Comparatively, previous analyses among women using fertility apps or cohort studies have reported that the mean or median cycle length for all women ranged between 28 and 30 days [ 8 , 11 , 33 , 34 ], and studies reporting on actual cycles reported means between 27.7 and 29.6 days [ 2 , 4 , 5 , 7 , 35 ]. These results cannot be extrapolated to an individual woman, and clinically, it is not helpful, as we have clearly demonstrated that the percentage of women with an average cycle length of 28 days is uncommon.…”
Section: Discussionmentioning
confidence: 97%
“…Data on aggregated cycles show mean cycle lengths of 28 to 29 days [ 2 , 3 ] and 29 to 30 days [ 4 - 7 ]. Other studies reporting on the number of women and their cycle length have demonstrated that 77% of women in the United States and Canada have a cycle length of 25 to 31 days [ 5 ]; 65% of rural Chinese women have a cycle length of 27 to 29 days [ 8 ]; and 84% of Australian women have a cycle length of 26 to 34 days [ 9 ]. Few studies also reported on the estimated day of ovulation, demonstrating an estimated day of ovulation at day 14 in only 3% to 10% of cycles [ 10 ] and at day 15 in 12% to 16% cycles [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Menarche can be delayed by genetic factors, hypothalamus-pituitary-ovarian axis abnormalities, undernutrition, hard physical exercise, psychological factors, or chronic disease. These factors affect not only the menarche but also subsequent fertility of the women [17,18].…”
Section: International Journal Of Reproductive Medicinementioning
confidence: 99%
“…Menstrual abnormalities include painful cramps (dysmenorrhea), heavy bleeding (menorrhagia), absence of menstruation (amenorrhea), light or infrequent menstruation (oligomenorrhea) and premenstrual syndrome (PMS)[2–8]. These can be caused by a range of factors, including hormonal imbalances, genetic factors, infection, stress, and clotting disorders [9, 10], and are associated with complications such as anemia, osteoporosis, and in severe cases, infertility [11]. Abnormal menstrual patterns caused by altered hormonal balance may mediate the risk of hypertension.…”
Section: Introductionmentioning
confidence: 99%